1.) A = [6, 1, -4, -6, 7, -7] B = [-5, -1, -3, -8, 6, 8]
-5A + 4B = -5[6, 1, -4, -6, 7, -7] + 4[-5, -1, -3, -8, 6, 8] = [-30, -5, 20, 30, -35, 35] + [-20, -4, -12, -32, 24, 32] = [-50, -9, 8, -2, -11, 67]
2.) 2X + 2[2, -8, -4, 2] = [4, -6, 2, -8]
2X + [4, -16, -8, 4] = [4, -6, 2, -8]
2X = [4, -6, 2, -8] - [4, -16, -8, 4] = [0, 10, 10, -12]
X = [0/2, 10/2, 10/2, -12/2] = [0, 5, 5, -6]
X = [0, 5, 5, -6]
3.)
[-5,-2, * [-5, 7, = [25 + 18, -35 + 10, = [43, -25,
-8, -5] -9, -5] 40 + 45, -56 + 25] 85, -31]
4.)
[1, 1, 4, * [9,
5, 6, 0] 1,
-7]
=> 2 x 3 * 3 x 1
since the inner dimensions is equal = 3, the product is defined and the dimension of the product is the outer dimensions 2 x 1